2017
DOI: 10.1097/mpg.0000000000001566
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Gestational Weight Gain With the Infant Fecal Microbiota

Abstract: Objectives Pregnancy characteristics may influence the infant fecal microbiota during early life. We aimed to examine associations of maternal gestational weight gain with infant fecal microbiota composition, bacterial community richness, and Shannon diversity index. Methods We analyzed data from a prospective cohort study of healthy infants. We collected prenatal data, including report of mother’s gestational weight gain, and infant fecal samples from 84 infant-mother dyads. By applying 16S rRNA gene sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
(92 reference statements)
2
18
0
Order By: Relevance
“…Table 1 lists data extracted from each study, including author, PICO statement, number of participants and biospecimens, time point of microbiome collection, and the data source (i.e., primary data collection in a cohort study or collection from a specimen biobank or repository). We have categorized studies in the table by population from which biospecimens were collected: five studies collected biospecimens from mothers only (Collado, Isolauri, Laitinen, & Salminen, 2008;Gomez-Arango et al, 2016a;Houttu, Mokkala, & Laitinen, 2017;Santacruz et al, 2010;Smid et al, 2018), four sequenced biospecimens from children only (Collado, Isolauri, Laitinen, & Salminen, 2010;Galley, Bailey, Kamp Dush, Schoppe-Sullivan, & Christian, 2014;Mueller et al, 2016;Robinson et al, 2017), and two included biospecimens from both mothers and their infants (Chu, Antony, et al, 2016;Stanislawski et al, 2017). The average time point for collection of maternal gastrointestinal microbiome biospecimens was 17.2 weeks' gestation (range ¼ 10À24 weeks' gestation), while two studies conducted followup microbiome collection at 30À39 weeks' gestation (range ¼ 30À39 weeks; Collado et al, 2008;Smid et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 lists data extracted from each study, including author, PICO statement, number of participants and biospecimens, time point of microbiome collection, and the data source (i.e., primary data collection in a cohort study or collection from a specimen biobank or repository). We have categorized studies in the table by population from which biospecimens were collected: five studies collected biospecimens from mothers only (Collado, Isolauri, Laitinen, & Salminen, 2008;Gomez-Arango et al, 2016a;Houttu, Mokkala, & Laitinen, 2017;Santacruz et al, 2010;Smid et al, 2018), four sequenced biospecimens from children only (Collado, Isolauri, Laitinen, & Salminen, 2010;Galley, Bailey, Kamp Dush, Schoppe-Sullivan, & Christian, 2014;Mueller et al, 2016;Robinson et al, 2017), and two included biospecimens from both mothers and their infants (Chu, Antony, et al, 2016;Stanislawski et al, 2017). The average time point for collection of maternal gastrointestinal microbiome biospecimens was 17.2 weeks' gestation (range ¼ 10À24 weeks' gestation), while two studies conducted followup microbiome collection at 30À39 weeks' gestation (range ¼ 30À39 weeks; Collado et al, 2008;Smid et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The average time point for collection of maternal gastrointestinal microbiome biospecimens was 17.2 weeks' gestation (range ¼ 10À24 weeks' gestation), while two studies conducted followup microbiome collection at 30À39 weeks' gestation (range ¼ 30À39 weeks; Collado et al, 2008;Smid et al, 2018). Only two of the studies used biospecimens from a common biobank or biorepository (Robinson et al, 2017;Stanislawski et al, 2017). Table 1 further provides operationalization of key variables across each of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that significant differences in gestational age, maternal pregnancy weight gain and gender between groups can influence the microbiome 21 , 29 , 42 . In this study, with a relative limited sample size, the impact of these factors was not concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were a transfer to a participating hospital >48 h after the original hospitalization, delayed consent (>24 h after hospitalization), gestational age ≤32 weeks, and known comorbidities (cardiopulmonary disease, immunodeficiency, immunosuppression). In addition, during the same period, we also enrolled 115 healthy infants as the controls (age-matched within 1.5 months of cases) [ 11 , 15 – 17 ]. We excluded infants with current fever, respiratory illness, or gastrointestinal illness, antibiotic treatment in the preceding 7 days, gestational age ≤32 weeks, or known comorbidities.…”
Section: Main Textmentioning
confidence: 99%
“…Taken together, a total of 155 infants were eligible for the current analysis. From these infants, by using a standardized protocol [ 11 , 15 , 17 ], investigators conducted a structured interview and medical record review, and collected fecal specimens at the time of hospitalization (cases) or at home before the clinic visit (controls). The fecal samples were immediately stored at −80 °C.…”
Section: Main Textmentioning
confidence: 99%